An approach of using different curing temperature based on potato cv. Innovator periderm differentiation, sugar metabolism, and industrial quality (Acta Scientiarum. Agronomy, 2022)
Excoriation damage is among the major causes of postharvest potato losses. Curing is known to increase the resistance of tubers to excoriation injury, with the temperature influencing the traumatic phellogen and periderm regeneration, as well as tuber processing quality. This study aimed to evaluate the effects of excoriation procedure and curing temperature on the industrial quality, histological characteristics, carbohydrate metabolism, and oxidative enzyme activity of potato tuber. Tubers with or without excoriation were cured at 8, 14, and 20°C for 15 days. Excoriation did not influence the levels of reducing sugars (RS), as well as polyphenoloxidase (PPO) and peroxidase (POD) activities. The concentrations of total soluble sugars (TSS) and non-reducing sugars (NRS) were higher in injured tubers, while reduction in curing temperature increased the concentrations of TSS, NRS, and RS. However, the sugar content was adequate as per the criteria of the pre-fried potato industry and potatoes classified in category 2 (USDA/fast-food industry color grading). The reduction in curing temperature also increased the activity of POD, despite the activity of PPO remaining unchanged. Formation of a closure layer from the outer parenchyma cells of the tuber that prevents desiccation and death of superficial cells, was observed. This protection was completed with the formation of the damage periderm. Periderm regeneration is faster at higher temperatures, 15 and 20°C, leading to a lower fresh mass loss and no enzymatic or non-enzymatic browning. The excoriation carried out at 14/20oC for 15 days was sufficient for curing, and for maintaining suitable post-fry quality of potatoes.